Motor imagery training in patients with chronic neglect: a pilot study - Leifert-Fiebach, Gundhild; Welfringer, Anouk; Babinsky, Ralf; Brandt, Tobias (NeuroRehabilitation, 2013)
Introduction: Only few studies have investigated the effects of motor imagery training (MIT) on neglect symptoms. Objective: To investigate the imagery ability of patients with visuospatial neglect and the behavioral effects of MIT on neglect symptoms. Methods:In an intense four-week course 10 patients with chronic visuospatial neglect symptoms resulting from right-hemisphere lesions practiced MIT by mentally envisaging positions and movements of the contralesional upper limb. Visual and kinesthetic MIT abilities as well as neglect-related disability were evaluated prior to and following therapy. Neglect symptoms were as well assessed at three-month follow-up. Results: Results suggest that (i) the ability to perform motor imagery is principally retained in patients with neglect and even patients that are seemingly incapable of motor imagery are able to relearn imagined activation via an individualized training approach. Furthermore, imagined activation of the left arm (ii) significantly reduces the severity of neglect in exploration, (iii) enhances temporal and spatial orientation, and (iiii) significantly improves the kinesthetic motor-imagery capacity and ability. These improvements were stable over a three-month period, indicating long-term training effects. Conclusion: Our data suggest that active kinesthetic-motor imagery is a feasible and effective training method for patients suffering from chronic visuospatial neglect symptoms.